The Association of Serum Lactoferrin Level with Psychological Symptoms, Cognition, and Executive Function in Schizophrenia Patients - Niloufar Mahdavi Hezaveh; Soheila Kianpour Rad; Yousef Semnani; Maryam Mousavi Bazaz; Abdolreza Javadi (Iranian Journal of Psychiatry)
Objective: Lactoferrin, a glycoprotein, has known neuroprotective effects, yet its role in the pathophysiology of neuropsychiatric disorders, particularly schizophrenia, remains unclear. This study aims to assess changes in lactoferrin levels during different phases of schizophrenia and explore its relationship with cognitive symptoms and performance. Method: This before/after interventional study involved 30 patients diagnosed with schizophrenia. Participants were evaluated at two time points: upon hospital admission and after the resolution of acute symptoms. The Positive and Negative Syndrome Scale (PANSS) was utilized to measure symptom severity, while the Brief Assessment of Cognition in Schizophrenia (BACS) assessed the neurocognitive function. Serum lactoferrin levels were quantified using the Enzyme-Linked Immunosorbent Assay (ELISA) method. Results: Serum lactoferrin levels significantly decreased from 130.63 ± 52.49 ng/mL at admission to 85.42 ± 29.03 ng/mL at discharge (P < 0.001). No significant correlation was found between lactoferrin levels and PANSS scores (r = 0.011, P = 0.975). However, an inverse correlation was observed between changes in lactoferrin levels and the executive function subscale of the BACS (r = -0.360, P = 0.050). Cognitive assessments indicated significant improvements in verbal memory (P = 0.033), working memory (P = 0.002), and executive function (P = 0.039) post-treatment. Conclusion: The study demonstrates a significant reduction in serum lactoferrin levels during the acute phase of schizophrenia, suggesting its potential role in modulating cognitive functions, particularly the executive function, rather than influencing positive or negative symptoms.